Analisis Variasi Temperatur Aktivasi terhadap Gugus Fungsi Arang Aktif Tandan Aren (Arenga Pinnata Merr.) dengan Agen Aktivasi Potassium Silicate (K2SiO3) - Hijrah, Nandini Nur; Anas, Muhammad; Erniwati, Erniwati (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to determine the effect of variations of the sugar palm activation temperature on the functional groups of activated charcoal from palm bunch (Arengga Pinnata Merr) with potassium silicate (K2SiO3) activation agent. The process of making an chemically activated charcoal is divided into three stages, firstly the preparation stage of preparing the palm bunches into cutting, washing and drying, secondly carbonitation stage at a temperature of 300oC – 400oC about ± 8 hours and the chemical activation stage. Potassium silicate K2SiO3 is a new activation agent that is used to activate an activated charcoal by using 2 : 1 ratio (K2SiO3: activated palm bunches) for 12 hours and an activation temperature of 600oC, 650oC, 700oC, 750oC, and 800oC for 30 minutes. Characterization of activated charcoal from palm bunches was tested by using Fourier Transform Infrared (FTIR). The FTIR spectrum shows that the activated charcoal produced has an absorption pattern with the types of bonds are C≡C (Alkuna), C=C (Aromatic Rings), C-H (Alkanes), Si-O and C-H (Alkanes). The Information was obtained that a good activation temperature for activated charcoal of palm  bunches was seen at temperatures of 650oC, 700oC and 750oC with the largest IR absorption was seen at temperatures of 700 oC.